Comparative Analysis of Accuracy to the Establishment of Three Dimensional Models from Diponegoro Prince Statue Using Close Range Photogrammetry Method in Non Metric Camera and Unmanned Aerial Vehicle (UAV) Technology. (August 2019) - Prasetyo, Y; Yuwono, B D; Barus, B R
Abstract: Diponegoro Prince Statue is one of the important icons in the campus area of Diponegoro University. Because the new statue is in the area of Widya Puraya. Therefore many people visit the statue. Diponegoro statue also experienced erosion by nature (wind, rain water, etc.). Therefore, it is necessary to preserve the Diponegoro statue so that it is not damaged and lost its existence by the times. In this research, two type of surveying instruments will be tested for their accuracy in the Diponegoro statue, namely non-metric cameras (NMC) and Unmanned Aerial Vehicle (UAV). The method used in this research is Close Range Photogrametry by comparing the results of the visualization of the model and testing the accuracy of the three-dimensional model with a comparison of the distance of the field measurements of the Total Station. From the results of visualization and accuracy of the three-dimensional model, it will be obtained which results are better between non-metric cameras and UAVs. The final results of this study indicate that UAV has a higher level of geometric accuracy compared to non-metric cameras. This is indicated by the results of the accuracy of the the UAV obtained a fairly good level of accuracy compared to the camera that is equal to 0.0162 ± 0.0133 meters for the statue of Prince Diponegoro. Whereas in non-metric cameras, the results of lower accuracy were 0.1615 ± 0.0593 meters in the statue of Prince Diponegoro. Based on the visualization of the three-dimensional model between the camera, UAV and NMC, it was found that UAV produced a better model compared to the three-dimensional model produced by NMC. With the results of the analysis in this study it is expected that the results of 3D modeling with cameras and UAVs can be used as an effort to preserve the Diponegoro statue.